Languages As Categories: Reframing the "One Language or Two" Question in Early Bilingual Development. Issue 2 (September 2014) - Byers‐Heinlein, Krista; Molnar, Monika; Sebastian‐Galles, Nuria
<x xml:space="preserve">Abstract</x> One of the most enduring questions in the field of bilingualism is whether bilingual infants and children initially have one language system or two. Research with adults indicates that, while bilinguals do not represent their languages in two fully encapsulated language systems, they are able to functionally differentiate their languages. This article proposes that bilinguals differentiate their languages insofar as they can treat elements of their languages as belonging to different categories. Several lines of research with bilingual adults and children are considered in the context of perceptual and conceptual language categories. The article ends with a discussion of how language categories might emerge over the course of early bilingual development and outlines directions for future research.